IPMN-associated pancreatic cancer: survival, prognostic staging and impact of adjuvant chemotherapy - Kaiser, Jörg; Scheifele, Cornelius; Hinz, Ulf; Leonhardt, Carl-Stephan; Hank, Thomas; König, Anna-Katharina; Tjaden, Christin; Hackert, Thilo; Bergmann, Frank; Büchler, Markus W.; Strobel, Oliver (European journal of surgical oncology, 2022)
Background - Intraductal papillary mucinous neoplasm (IPMN)-associated carcinoma is a subtype of pancreatic cancer for which prognostic factors, the validity of the AJCC/UICC staging system and the role of adjuvant chemotherapy remain unknown. - Materials and methods - Clinicopathological, treatment and follow-up data of patients with IPMN-associated carcinoma undergoing resection between 2002 and 2018 were analyzed. Uni- and multivariable survival analyses were performed to identify prognostic factors. - Results - Of 424 patients undergoing resection for IPMN-associated carcinoma, 77% patients had pancreatic ductal adenocarcinoma (IPMN-PDAC) and 23% had colloid carcinoma (IPMN-CC). Compared to IPMN-CC, IPMN-PDAC was diagnosed at more advanced tumor stages, more frequently involved lymph nodes, more frequently showed poor differentiation and were associated with higher rates of R1 resections. Resected IPMN-PDAC showed markedly shorter median overall survival than IPMN-CC (26.7 months vs. 91.3 months). The current AJCC/UICC staging system was validated for IPMN-associated carcinoma and for both of its subtypes. In multivariable analysis age ≥70 years, diabetes mellitus, high levels of Ca 19-9, IPMN-PDAC subtype, G3 tumors and higher AJCC/UICC stage were independently associated with shorter survival. Adjuvant therapy was not associated with improved survival in IPMN-associated carcinoma. Overall survival was comparable in patients receiving vs. not receiving adjuvant therapy. - Conclusions - Survival after resection of IPMN-associated carcinoma depends on tumor stage, on histologic tumor subtype, grading, and Ca 19-9 levels. The current 8th edition of the AJCC/UICC staging system is applicable for IPMN-associated carcinoma and for both of its subtypes IPMN-PDAC and IPMN-CC. The role of adjuvant therapy for IPMN-associated carcinoma remains unclear.
Erstmals am 11. Dezember 2021 online zugänglich
Gesehen am 21.12.2022